Cultural diversity and new firm formation in China. Issue 10 (3rd October 2019) - Sun, Bindong; Zhu, Pan; Li, Wan
ABSTRACT: Using data on new private firm formation in prefectural cities in China in 2008 and internal migration of Chinese people in 2000, this paper examines to what extent cultural diversity can explain the regional variation of entrepreneurship. The results indicate that, holding other factors constant, cultural diversity vigorously promotes new private firm formation, especially in the manufacturing industry and for small firms . We address the endogeneity of cultural diversity by applying instrumental variables methods and confirm the relative robustness of this result.